2018
DOI: 10.1038/s41419-018-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch-induced osteogenic differentiation of human jaw bone marrow mesenchymal stem cells (hJBMMSCs) via inhibition of the NF-κB pathway

Abstract: Severe malocclusion can contribute to several serious dental and physical conditions, such as digestive difficulties, periodontal disease, and severe tooth decay. Orthodontic treatment is mainly used to treat malocclusion. Forces in orthodontic tooth results in bone resorption on the pressure side and bone deposition on the tension side. Osteoblasts have been considered as the key component in bone regeneration on the tension side. However, the underlying mechanisms remain unclear. In this study, we focus on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The CBFα subunits are encoded by the RUNXs, which contain 3 members: RUNX1, ‐X2, and ‐X3 (29, 30). RUNX1 is responsible for early MSC commitment toward the chondrogenic lineage, whereas RUNX2 mediates the initial steps of terminal chondrocyte maturation, hypertrophy, and mineralization (3133). Therefore, the particular levels of phospho‐JNK/ β‐catenin might also mediate the prochondrogenic and antiossific effects of KGN preconditioning by interfering with the balance of RUNX1/2.…”
Section: Discussionmentioning
confidence: 99%
“…The CBFα subunits are encoded by the RUNXs, which contain 3 members: RUNX1, ‐X2, and ‐X3 (29, 30). RUNX1 is responsible for early MSC commitment toward the chondrogenic lineage, whereas RUNX2 mediates the initial steps of terminal chondrocyte maturation, hypertrophy, and mineralization (3133). Therefore, the particular levels of phospho‐JNK/ β‐catenin might also mediate the prochondrogenic and antiossific effects of KGN preconditioning by interfering with the balance of RUNX1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been shown that the NF‐κB signaling acts as a negative regulator of osteoblast differentiation and bone formation (Kim et al, 2017; Li et al, 2015; Mishra et al, 2020; Novack, 2011). Chen, Liu et al (2018) found that mechanical stretch induced osteogenic differentiation of human bone marrow mesenchymal stem cells via inhibition of NF‐κB signaling. We herein clarified the role of NF‐κB signaling in stretch‐induced osteogenic differentiation in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB is found to be a negative regulator of osteoblastic differentiation and bone formation (Chang et al, 2009; Krum et al, 2010; Novack, 2011). It has been shown that mechanical stretch promotes osteogenic differentiation in bone marrow mesenchymal stem cells and osteoblasts by inhibiting the NF‐κB activity (Chen, Liu, et al, 2018; Xu et al, 2020). However, the role of either mTOR or NF‐κB in the regulation of stretch‐induced osteogenic differentiation in osteoblasts remains not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is a major transcription factor that regulates the expression of inflammatory mediators and cytokines, and its activation plays a critical role in the initiation and development of inflammatory bone disease, suggesting that the inhibition of NF-κB signaling could represent a promising therapeutic target for the inhibition of osteolysis. Although the effects of NF-κB activation on osteoblast differentiation and bone formation under in vitro culture conditions remain under debate, in general, NF-κB activation has been implicated in the stimulation of osteoclast differentiation and the inhibition of osteogenic differentiation in MSCs [23][24][25][26]. Chang et al [27] reported that the time-and stage-specific inactivation of NF-κB signaling in differentiated osteoblasts significantly increased trabecular bone mass and bone mineral density, without affecting osteoclast activities in young mice, and rescued bone loss in an ovariectomized adult mouse model.…”
Section: Discussionmentioning
confidence: 99%